DEVELOPMENT OF ENRICHMENT BOOK FOR MATHEMATICS LEARNING OF NUMBER CONTENT FOR JUNIOR HIGH SCHOOL STUDENTS BASED ON PROBLEMS IN REAL WORLD CONTEXTS - Amaliah, Sani
The learning process plays a crucial role in improving students' behavior, knowledge, skills, and attitudes. Mathematics education, in particular, is essential in shaping logical and critical thinking patterns, as well as helping students solve everyday problems. However, the 2018 PISA results indicate that only 1% of Indonesian students were able to model and solve contextual problems, compared to the OECD average of 11%. Additionally, the 2019 National Examination for Junior High Schools and the 2023 Minimum Competency Assessment (AKM) revealed low numeracy skills among junior high school students, particularly in the number content standard. Based on these findings, the development of a supplementary mathematics book titled Mathematics with Number Content in Real- World Contexts using the Problem in Real-World Context (PRWC) approach was undertaken to enhance students' mathematical literacy in number content. The PRWC method, which has been applied in Singapore, is designed to help students tackle and solve everyday problems mathematically. The development of this book aims to improve students' mathematical literacy and problem-solving skills in realworld contexts, thus better preparing them to face future challenges. The ADDIE methodology was used as the framework for developing the book, encompassing the stages of Analysis, Design, Development, Implementation, and Evaluation. After the book was completed, it was tested on students who had gone through the D Phase of the Merdeka Curriculum to assess its feasibility and its impact on students' understanding of number content. The feasibility test results showed that ten indicators of book feasibility were met, indicating that the book is suitable for use. The evaluation of the book's impact demonstrated a positive effect, with an average score increase of 83%. This score difference indicates an improvement in student performance after the book was implemented